Effects of poultry manure on soil infiltration, organic matter contents and maize performance on two contrasting degraded alfisols in southwestern Nigeria - Adebayo. J. Adeyemo; Omowunmi O. Akingbola; Stephen O. Ojeniyi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This research work described the effect of organic waste (poultry manure) on soil cumulative infiltration rate (CIR), soil organic matter (SOM), and maize performance on two contrasting alfisols of southwestern Nigeria. Method Six treatments of poultry manure were applied in split at 0 Mg/ha, 2 Mg/ha, 4 Mg/ha, 6 Mg/ha, 8 Mg/ha, and 10 Mg/ha, in replicate under a completely randomized design to clay loam (CL) and sandy clay loam (SCL) soils, at 3, 6, 9, and 12 weeks after the initial application. Results The results showed significant increases (Pâ<â0.05) in CIR, SOM, and maize performance compared to the control in both soils. Poultry manure at 10 Mg/ha recorded the highest SOM which was significantly (Pâ<â0.05) different from other application rates in both soils. The mean values for SOM in SCL were between 0.67 and 3.75% for 0 Mg/ha and 10 Mg/ha, while the mean values recorded for CL were between 0.80 and 4.35% at 0 Mg/ha and 10 Mg/ha. Poultry manure reduced CIR in the SCL, but improved CIR with increasing rates on CL. Poultry manure at 4â10 Mg/ha increased the maize shoot biomass significantly (Pâ<â0.05). However, the application rate of 6 Mg/ha manure recorded the highest fresh shoot biomass, while 8 Mg/ha increased dry shoot biomass in both soils. Conclusion This study indicated that poultry manure applied at 10 Mg/ha gave the best results in improving CIR, SOM, and maize performance on different soil types.